The Influence of Open, Semi-Closed, and Closed House Microclimates on Broiler Productivity in the Dry Season - Hamiyanti, Adelina Ari; Nurgiartiningsih, Veronica Margareta Ani; Muharlien, Muharlien; Suyadi, Suyadi (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2023)
In Indonesia, there are three housing systems: sometimes open, semi-closed and closed. This study aimed to analyze the effect of microclimatic conditions, NH3, and E. coli levels on broiler productivity in open, semi-closed, and closed houses during the dry season. The research took place in June - August 2019, when the air temperature was 28°-34°C during the day, while at night, the air temperature was around 21°-25°C with rainfall < 60 mm/month. The material used was the Lohmann strain broiler. Observations were made in six house units consisting of two open house units with a total of 5,000 chickens/house unit, two semi-closed units with a total of 18,000 chickens/house unit, and two closed house units with a total of 33,000 chickens/house unit. This research is survey research, with the experimental parameters being temperature (oC), humidity (%), wind speed (m/s), NH3 (ppm) and E. coli (CFU/mL), body weight (g/bird), FI (g/bird/day), FCR, IP, mortality, and IOFC. Based on the study's results in open, semi-closed, and closed houses, there were differences (P<0.05) in temperature, humidity, wind speed, and NH3, whereas in E. coli they were not significantly different. In broiler productivity, the type of house affected body weight (P<0.05), while on FI, FCR, IP, mortality, and IOFC were not significantly different (P<0.05). The conclusion is that the range of temperature, humidity, and wind speed in all houses is still in the standard range of broiler maintenance. NH3 and E. coli levels were below the threshold that chickens could tolerate, although the highest levels were in closed houses. This affects the BW of broilers in open and semi-closed at weeks 1, 2, and 3, which is higher than in closed houses